2021
DOI: 10.1680/jgrma.20.00013
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-mode fracture behavior of 3D-printed PLA with zigzag filling

Abstract: Polylactic acid (PLA) is a widely used biomaterial in medical applications as a biodegradable and renewable aliphatic polyester type of material. This material is often subjected to different defects and damages from in-service and manufacturing conditions, and the increasing demand for PLA for different applications requires a thorough understanding of its fracture behavior. In this work, a numerical and experimental study of the mixed-mode fracture behaviors of three-dimensional (3D)-printed PLA samples with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This material property is used in the design to characterize the resistance to fracture. The stress intensity factor K C at the tip of a crack in a specimen is given by Torun et al (2020), Oskui et al (2016); and Yayla (2019):…”
Section: Stress Intensity and Geometrical Factors Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…This material property is used in the design to characterize the resistance to fracture. The stress intensity factor K C at the tip of a crack in a specimen is given by Torun et al (2020), Oskui et al (2016); and Yayla (2019):…”
Section: Stress Intensity and Geometrical Factors Calculationmentioning
confidence: 99%
“…Rahmani et al (2019) investigated the fracture toughness, delamination strength and fractography of the fracture surface of CF reinforced polymer-based composites between À80 and 122°C experimentally and numerically using Arcan fixture. Torun et al (2020) conducted mixed-mode fracture tests on PLA samples processed with a zigzag pattern at different filling rates on a 3D printer. They found that, by increasing the loading angle, the Mode I geometric function value decreased and the Mode II stress intensity factor value increased.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the fracture behavior of materials under varying conditions, such as different fabrication parameters and loading conditions, is crucial for their use as structural elements (Hossein Abadi et al , 2020). Additive manufacturing has facilitated the production of samples with specific configurations and crack lengths for investigating the fracture behavior (Hossein Abadi et al , 2020; Torun et al , 2020; Linul et al , 2020; Brugo et al , 2016; Cano et al , 2018). Studies have commonly examined the mixed-mode fracture behavior of fused deposition modeling (FDM) printed parts.…”
Section: Introductionmentioning
confidence: 99%
“…Similar methods were used to study the fracture behavior of samples fabricated using the FDM technique. Recently, Torun et al (2020) fabricated 3D-printed polylactic acid (PLA) samples with a zigzag layout to investigate the effects of filling ratios on mixed-mode fracture behavior. The authors observed that for all filling ratios, the shear mode stress intensity factor (SIF) increased with the loading angle from 0° to 90°, while the opening mode critical SIF decreased.…”
Section: Introductionmentioning
confidence: 99%
“…They determined that the chitosan reinforcement and the filling density were important parameters in the strength of composite specimens, but the annealing temperature did not affect it much. Torun et al (2020) produced zigzag printed PLA samples to examine the effects of filling ratios on the mixed-mode fracture behavior of 3D printer components. For all filling ratios, they reported that when the loading angle was increased from 0° to 90°, the shear mode stress intensity factor increased and the tension (opening) mode critical stress intensity factor decreased.…”
Section: Introductionmentioning
confidence: 99%